Continuously high reactive oxygen species generation decreased the specific ϵ-poly-l-lysine formation rate in fed-batch fermentation using glucose and glycerol as a mixed carbon source. Issue 12 (December 2015) - Zeng, Xin; Chen, Xu-Sheng; Gao, Yang; Ren, Xi-Dong; Wang, Liang; Mao, Zhong-Gui
Graphical abstract: Highlights: ϵ-PL fed-batch culture with mixed carbon source showed deterioration after feeding approach. The glucose-glycerol mixed carbon source resulted in excessive oxidative stress. The oxidative stress caused biomolecules damage and cell physiological deterioration. The low antioxidant capacity further worsened the oxidative stress situation. Transcriptome analysis confirmed the stress existence in the mixed carbon source. Abstract: A glucose–glycerol mixed carbon source led to higher production of both ϵ-poly-l -lysine and biomass, whether in the batch or fed-batch fermentation. However, as the major benefit of the mixed carbon source, the high specific ϵ-poly-l -lysine formation rate in the batch fermentation sharply declined when the feeding strategy was initiated. In this study, we examined the development of cell physiology in ϵ-poly-l -lysine production to obtain an insight into this undesirable phenomenon. The simultaneous consumption of glucose and glycerol generated abundant reactive oxygen species in the batch fermentation stage. Transcriptome analysis further confirmed the existence of excessive oxidative stress with the glucose–glycerol mixed carbon source. Serious oxidative damage in the mixed carbon source resulted in deterioration in cell viability, intracellular levels of ATP andl -lysine in the following fed-batch fermentation. Moreover, the stress situation was worsened by a low antioxidant capacity with the mixed carbon source. As a result, these damaged cells showed decreased specific ϵ-poly-l -lysine formation rate. This study provided information for the understanding of the underlying change of cell physiology in ϵ-poly-l -lysine fed-batch fermentation, which was greatly needed for a further enhancement of ϵ-poly-l -lysine production in culture with an intensive cell respiration.